Maternal Behavior Affects Child’s Attachment-Related Cortisol Stress Response - Franziska, Köhler-Dauner; Jörg, M. Fegert; Anna,, Buchheim; Sabrina, Krause; Harald, Gündel; Christiane, Waller; Ute, Ziegenhain (Journal of Child and Adolescent Psychiatry, 2019)
Background Mothers with a history of childhood maltreatment (CM) are likely to transmit their own experiences to the next generation. This is highly influenced by the quality of maternal behavior that enables to buffer infant’s hypothalamic-pituitary-adrenal (HPA) axis response to stress. From a transgenerational perspective the research question is, if infant’s cortisol stress response is influenced by maternal CM experiences or rather by the behavioral pathways during the first year of life. Methods 53 mother-child-dyads were measured at 12 months of infant’s age in a laboratory visit assessing the maternal quality of interactive behavior using the Atypical Maternal Behavior Instrument for Assessment and Classification (AMBIANCE) measured during the strange situation procedure (SSP). Maltreatment experiences were assessed using the childhood trauma questionnaire (CTQ). Salivary cortisol of mother and infant were collected prior to and directly, 15 and 30 minutes after the SSP. Results Infants of disruptive mothers showed a significant increase in cortisol (F (3; 147) = 2.897, p= 0.048) after the SSP compared to infants of mothers with sensitive caregiving. Maternal CM did not influence the infant’s cortisol stress response due to the SSP. However maternal cortisol response was altered by trend due to CM (F (1.392; 71.008) = 3.157, p= 0.066). Conclusions Our data indicate that infant’s cortisol stress reactivity is influenced by the quality of maternal behavior and not by the transgenerational transmission of maternal CM experiences per se. These findings implicate that helping mothers to improve their caregiving behavior may help to improve stress-reactivity of their infant.
Keywords: Maternal behavior; adverse childhood experiences; cortisol stress response; infant’s hypothalamic-pituitary-adrenal (HPA)